Hippocampal integrity and neurocognition in first-episode schizophrenia: A multidimensional study. (April 2014) - Hasan, Alkomiet; Wobrock, Thomas; Falkai, Peter; Schneider-Axmann, Thomas; Guse, Birgit; Backens, Martin; Ecker, Ullrich K. H.; Heimes, Janina; Galea, Joseph Michael; Gruber, Oliver; Scherk, Harald
Abstract Objectives. Impairments in memory and executive function are key components of schizophrenia. These disturbances have been linked to several subcortical and cortical networks. For example, anatomical and functional changes in the hippocampus have been linked to deficits in these cognitive domains. However, the association between hippocampal morphometry, neurochemistry and function is controversial. Therefore, we aimed to investigate the relationship between hippocampal anomalies and their functional relevance. Methods. Fifty-seven first-episode schizophrenia patients (FE-SZ) and 61 healthy control subjects (HC) participated in this study. Hippocampal volumes were investigated using structural magnetic resonance imaging (sMRI) and hippocampal neurochemistry was determined using proton magnetic resonance spectroscopy (1H MRS). Verbal memory was used as a hippocampus-dependent cognitive task whereas working memory and cognitive flexibility assessed frontal lobe function. Results. FE-SZ presented smaller volumes of the left hippocampus, with a significant correlation between left hippocampal volume and verbal memory performance (immediate recall). There was also an inverse correlation between neurochemical ratios (NAA/Cho and Cho/Cr) and verbal memory (delayed recognition). Tests of cognitive flexibility and working memory were not correlated with MRI and 1H MRS values. Compared to HC, FE-SZ demonstrated reduced performance in all of the assessed neurocognitive domains. Conclusions. These results point to a relationship between verbal memory and hippocampal integrity in schizophrenia patients which might be independent from deficits in other memory domains. Disturbed verbal memory functions in FE-SZ might be linked specifically to hippocampal function.